Influence mechanism of K2SO4 addition on microstructure, mechanical properties and abrasion resistance of Fe-2wt%B alloy. (1st January 2021) - Yi, Yanliang; Li, Qiang; Huang, Xiaoyu; Zheng, Baochao; Liu, Yangzhen; Tu, Xiaohui; Li, Wei
Abstract: Fe2 B-type boride exists in Fe–B alloy with a form of netlike, rod-shaped, or fishbone structure. This results in high susceptibility of alloy to fracture. To improve the morphology of Fe2 B, various contents of K2 SO4 are added into an Fe-2wt%B alloy. The microstructure, mechanical properties and abrasion resistance of the modified alloy have been analyzed systematically.The results show that the α-MnS forms in the alloy, and increases with the increased K2 SO4 in a relationship of y  = 1.68 × + 0.03. Moreover, the α-MnS can act as effective heterogeneous nuclei of M2 B (where M represents Cr, Mn, and Fe), owing to a low lattice misfit of (111)α-MnS //(110)M2B . Meanwhile, the addition of element K can result in the formation of adsorbed film (K + film) on the surface of M2 B. By the joint action of α-MnS and K + film, the structure of M2 B changes from net-like into isolated block-shaped after heat treatment, and the shape factor K value of M2 B increases from 0.13 to 0.44 with an increment of 241%. The change of M2 B morphology effectively promotes an improvement of impact toughness and abrasion resistance of the alloy as a result. Graphical abstract: Unlabelled Image Highlights: As the K2 SO4 content increases from 0 to 3.57 wt%, the shape factor K value of M2 B (where M represents Cr, Mn, and Fe) can increase from 0.13 to 0.44 with an increment of 241%. With the increase of K2SO4 content, the fracture toughness of alloy changes from 6.09 to 14.72 J/cm2 with an increment of about 140%. The wear rate of alloy decreases rapidly when the K value is less than 0.2, while it trends to flat gradually as long as the K value exceeds 0.2.